Critical review of mercury methylation and methylmercury demethylation rate constants in aquatic sediments for biogeochemical modeling. Issue 24 (28th September 2022) - Helmrich, Stefanie; Vlassopoulos, Dimitri; Alpers, Charles N.; O'Day, Peggy A.
Abstract: Mercury is a toxin that causes neurological impairments in adults, is particularly harmful for fetuses and children, and is deadly in severe cases, making it a worldwide health concern. Methylmercury (MeHg) is the environmentally relevant form of mercury (Hg) because it biomagnifies along the food chain. Methylmercury is mainly produced in aquatic sediments via methylation of inorganic Hg (Hg(II)) and transformed back via demethylation. Because transformation rates determine MeHg concentrations, quantification of methylation and demethylation rates is needed to inform management of MeHg. Published rate constants for Hg(II) methylation ( k m ) and MeHg demethylation ( k d ) vary greatly, stemming partly from differences in experimental methods. We conducted a comprehensive review of rate laws, evaluated published rate constants, and performed biogeochemical simulations to assess variability in reported k m and k d . Based on selected studies employing the same pseudo-first-order rate law and similar experimental methods, we found that k m = 0.04 ± 0.03   d − 1 is a reasonable range for wetland sediments. Over a number of environments, maximum k d was smaller at sites without Hg source ( k d = 0.5   d − 1 ) than at sites with identified Hg source ( k d = 1.8   d − 1 ). Larger variability and higher uncertainty in k d compared to k m highlight the need for more research on MeHg demethylation rates. This critical review: (a) aids the design of future experimental studies of k m and k d ; (b) provides guidance for comparing rate constants from different studies; (c) presents a biogeochemical reaction model to assess rate constants; and (d) informs selection of k m and k d values from the literature for use in model simulations. Graphical abstract: UF0001